1990
DOI: 10.1152/ajprenal.1990.258.4.f973
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water intake on the progression of chronic renal failure in the 5/6 nephrectomized rat

Abstract: This study tests the possible influence of the urinary concentrating process and/or of vasopressin (AVP) on the progression of early chronic renal failure (CRF). Male Sprague-Dawley rats were submitted to 5/6 nephrectomy and were offered water ad libitum throughout the study. In addition, half of the rats (high water intake, HWI) received their food mixed with a water-rich agar gel. The other rats (normal water intake, NWI) ate the same amount of food plus agar in the usual dry powder form. This resulted in do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
150
2
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(161 citation statements)
references
References 0 publications
6
150
2
3
Order By: Relevance
“…Similar to our findings, Levine et al found no difference between db/db and wild type mice three weeks after uninephrectomy (Levine et al, 2008). However, we observed that the V2R antagonist treatment slightly attenuated kidney hypertrophy in the uninephrectomized db/db mice, consistent with its other renal effects and in agreement with previous studies in rats (Bouby et al, 1990;Bardoux et al, 2003b).…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Similar to our findings, Levine et al found no difference between db/db and wild type mice three weeks after uninephrectomy (Levine et al, 2008). However, we observed that the V2R antagonist treatment slightly attenuated kidney hypertrophy in the uninephrectomized db/db mice, consistent with its other renal effects and in agreement with previous studies in rats (Bouby et al, 1990;Bardoux et al, 2003b).…”
supporting
confidence: 93%
“…This effect of dDAVP does not occur in subjects with loss of function mutations in V2R (Bardoux et al, 2003a). In renal diseases, activation of V2R was shown to participate in the progression of renal failure in rats with five-sixth reduction in renal mass (Bouby et al, 1990). In a rat model of type 1 diabetes, vasopressin was shown to contribute to microalbuminuria through its V2R activation (Bardoux et al, 2003b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second experiment, we studied the effect of restoring urine concentrating activity by chronic infusion of a V2 agonist in 5/6 nephrectomized Brattleboro rats (which are devoid of endogenous vasopressin). Both these experiments showed that rats with the lowest urine concentrating activity displayed the slowest progression of chronic renal failure as assessed by the reduction in proteinuria, kidney hypertrophy, incidence of glomerulosclerosis and mortality (Bouby et al, 1990 (Figure 6). In another study, it has been shown that Brattleboro rats, unlike normal rats, do not present any increase in the single-nephron glomerular hyperfiltration rate after 5/6 nephrectomy (Bregman et al, 1990).…”
Section: European Journal Of Clinical Nutritionmentioning
confidence: 94%
“…Left: Sprague-Dawley rats with 5/6 nephrectomy were given an increased water intake for 10 weeks by mixing a water-rich agar gel with their feed (open dots) and were compared to rats with similar initial renal impairement but normal water intake (closed dots). Mean7SEM, nÂŒ9 rats per group at the beginning of the experiment, three rats in each group died or were killed during weeks 6-7, adapted from Bouby et al (1990). Right: Brattleboro rats with 5/6 nephrectomy were given an i.p.…”
Section: European Journal Of Clinical Nutritionmentioning
confidence: 99%